On the microstructure and texture evolution in 17-4 PH stainless steel during laser powder bed fusion: Towards textural design. (1st August 2022) - Moyle, M.S.; Haghdadi, N.; Liao, X.Z.; Ringer, S.P.; Primig, S.
Highlights: LPBF of 17-4 PH stainless steel is shown to result in a mainly δ-ferrite microstructure. Reducing the time between adjacent laser passes results in an increase in austenite volume fraction. Irrespective of printing parameters grains show a 〈100〉 texture in scanning direction. A model is proposed for the mosaic structure observed in cubic phases after LPBF. Abstract: Additive Manufacturing (AM) of metals allows the production of parts with complex designs, offering advanced properties if the evolution of the texture can be controlled. 17-4 precipitation hardening (PH) stainless steel is a high strength, high corrosion resistance alloy used in a range of industries suitable for AM, such as aerospace and marine. Despite 17-4 PH being one of the most common steels for AM, there are still gaps in the understanding of its AM processing–structure relationships. These include the nature of the matrix phase, as well as the development of texture through AM builds under different processing conditions. We have investigated how changing the laser power and scanning strategy affects the microstructure of 17-4 PH during laser powder bed fusion. It is revealed that the matrix phase is δ-ferrite with a limited austenite presence, mainly in regions of the microstructure immediately below melt pools. Austenite fraction is independent of the printing pattern and laser power. However, reducing the time between adjacent laser passes during printing results in an increase in the austenite volume fraction. Another effect of the higher laser power, as well as additional remelting within the printing strategy, is an increase in the average grain size by epitaxial ferrite grain growth across multiple build layers and the development of a mosaic type microstructure. Changes to the scanning strategy have significant impacts on the textures observed along the build direction, while 〈100〉 texture along the scanning direction is observed consistently. Mechanisms for texture formation and the mosaic structure are proposed that presents a pathway to the design of texture via AM process control.